Pengaruh Pelatihan Pemaafan terhadap Kesejahteraan Subjektif pada Ibu Yang Bekerja - Yuliana Yuliana; Alimatus Sahrah; Moordiningsih Moordiningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Working mothers, having a dual role as a housewife and a worker outside the home is certainly not an easy thing to do because working mothers are faced with two demands that must be carried out simultaneously and must be fulfilled in a balanced way, which if these demands are not met will cause conflict that has an impact on decreased well-being, stress and decreased positive emotions and increased negative emotions. The purpose of this study was to determine the effect of forgiveness training on the subjective well-being of working mothers. The research design used a pretest posttest control group design experiment with 32 subjects divided into 16 people as the experimental group and 16 people as the control group using random assignment. Data collection used the Satisfaction with Life Scale (SWLS) and the Scale of Positive and Negative Experience (SPANE) to measure subjective well-being. Data analysis used the non-parametric Mann Whitney test and the Wilcoxon test. The results of the analysis showed a p value = 0.000 (p <0.05), so it can be concluded that forgiveness training has an influence in increasing the subjective well-being of working mothers.